2009
DOI: 10.1124/mol.108.053322
|View full text |Cite
|
Sign up to set email alerts
|

Direct Subunit-Dependent Multimodal 5-Hydroxytryptamine3Receptor Antagonism by Methadone

Abstract: Homomeric 5-hydroxytryptamine (5-HT) 3A and heteromeric 5-HT 3AB receptors mediate rapid excitatory responses to serotonin in the central and peripheral nervous systems. The alkaloid morphine, in addition to being a -opioid receptor agonist, is a potent competitive inhibitor of 5-HT 3 receptors. We examined whether methadone, an opioid often used to treat morphine dependence, also exhibited 5-HT 3 receptor antagonist properties. Racemic (R/S)-methadone inhibited currents mediated by human homomeric 5-HT 3A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…R -methadone thus seems to be the major stereoisomer involved in pain relief and the prevention of opioid withdrawal. S -methadone (or d -isomer) is an antagonist of the NMDA receptor [27] and also inhibits the reuptake of 5-hydroxytryptamine [28]. S -methadone blocks the human ether-à-go-go-related gene (hERG) voltage-gated potassium channel more potently, which can cause drug-induced long QT syndrome, leading to potentially lethal ventricular tachyarrhythmia [29].…”
Section: Discussionmentioning
confidence: 99%
“…R -methadone thus seems to be the major stereoisomer involved in pain relief and the prevention of opioid withdrawal. S -methadone (or d -isomer) is an antagonist of the NMDA receptor [27] and also inhibits the reuptake of 5-hydroxytryptamine [28]. S -methadone blocks the human ether-à-go-go-related gene (hERG) voltage-gated potassium channel more potently, which can cause drug-induced long QT syndrome, leading to potentially lethal ventricular tachyarrhythmia [29].…”
Section: Discussionmentioning
confidence: 99%
“…In another study Das and Dillon (2005) using murine receptors reported an ∼40 fold difference in the IC 50 values of PTX (5-HT 3 A, 41 μM; 5-HT 3 AB, 1.1 mM), and also showed that an M2 residue (6′) was a common determinant of PTX inhibition. Thus, while it is possible that the difference in potency is due to different behaviours at these two subtypes, as, for example, has been described for methadone (Deeb et al., 2009), we speculate that the mechanisms of action of the structurally-related gingkolide compounds are similar in homomeric and heteromeric receptors, and it is the different pore lining residues that are the cause of the different potencies.…”
Section: Discussionmentioning
confidence: 99%
“…Methadone, an opioid often used to treat morphine addiction, also competitively inhibits human 5-HT 3 A receptors and increases desensitization. However, an insurmountable block was observed for heteromeric human 5-HT 3 AB receptors [34*]. …”
Section: Other Compoundsmentioning
confidence: 99%